Eksistensi Hak Ulayat Masyarakat Adat di Kota Jayapura dalam Konteks Ancaman Penyerobotan Tanah - Tri Mulyadi; Muhammad Yusuf; Hendrik Dengah (Pusat Riset dan Inovasi Nasional, 2025)
The customary land rights (hak ulayat) of indigenous communities in Jayapura City represent cultural identity with legal, social, spiritual, and ecological dimensions. However, their existence faces serious threats due to land grabbing practices by corporations, state-driven development policies, and individuals supported by biased regulations. This study employs a normative legal method with statutory, conceptual, and case approaches to examine the dynamics of hak ulayat protection. Findings indicate that although the 1945 Constitution and the Basic Agrarian Law recognize customary land rights, their implementation remains weak due to overlapping sectoral regulations, unfavorable legal pluralism, and the dominance of investment interests. These conditions place indigenous peoples in a subordinate position, leading to the loss of living space, cultural identity, and increased vulnerability to conflict. Legal protection efforts are required through regulatory strengthening, customary land inventory, the application of the principle of free, prior, and informed consent (FPIC), and the active role of judiciary and civil society. Such measures are essential to safeguard hak ulayat as cultural heritage and an instrument of social justice while preventing the recurrence of land grabbing practices that disadvantage indigenous communities in Jayapura City.